Sistem Monitoring Online Dan Analisis Perfomansi Plts Panel Surya Monocrystalline 100 Wp Berbasis Web - Duanaputri, Rohmanita; Heryanto/Eryk, Irwan; Sajidan, Muhammad Firas; Ayusta Lukita Wardani; Hakim, Muhammad Fahmi (Elposys: Jurnal Sistem Kelistrikan, 2023)
In this modern life, people's dependence on energy sources, especially electrical energy, has led to innovation in the use of cheap alternative energy sources that are environmentally friendly such as solar energy, one of which is PLTS. To support PLTS performance, a web-based monitoring system is needed for remote monitoring in monitoring PLTS performance, the data displayed is the result of measurements by voltage and current sensors installed in each solar panel on the PLTS performance detector. In this case, it is necessary to develop a Web-based monitoring system to help improve the efficiency of performance maintenance on 100 wp monocrystalline panels. By using the INA260 sensor in the form of a digital DC sensor that can measure a maximum current of 15 A, a maximum voltage of 36 v, and DC power and the DS18B20 sensor is a digital sensor that can measure the surface temperature of the panel. Sensor readings can be displayed offline via the HMI LCD while online readings can be displayed in the form of a Web which has a graphical display feature for each parameter and downloads data in the form of a .csv file as a feature that supports data analysis. The results of the sensor validation test or calibration using a measuring instrument have an average error sensor reading of 0.34 %. The average current sensor error is 0.63%, and the power sensor error average is 0.56%, while the average panel surface temperature sensor error is 0.34%